Elaboração e aplicação preliminar do instrumento para Avaliação da Funcionalidade e Incapacidade na Infância - IAFII - Alves, Cristiane Paiva (Universidade Federal de São Carlos, 2010)
The early identification problems in the development of physical, psychic and social abilities, in thepreschool phase, can contribute for intervention procedures. The child with physical deficiency faces,daily, challenges for learning in the process of school inclusion. Considering this a reality, the presentresearch aimed to describe the influence of interaction among the components of the ICF-CY. In theevaluation process of functionality and incapacity in children with physical deficiency, originated fromthe sequels of prematurity in the process of school inclusion for the preschooler. For that, it waselaborated a preliminarily called instrument, Instrument for the Evaluation of Functionality andIncapacity in Infancy, for children of 3 until 6 years (IAFII). It was performed a study case, object of thepresent study, to verify the relevancy of the proposal of the instrument and the feasibility of the plan. Inthis study 3 children in process of preschool inclusion were selected, from the feminine sex. C1, 4 yearsold; C2, 6 years old; and C3, 5 years old. Preterm born, diagnosticated with hemiparesy spastic cerebralpalsy. And theirs care givers. The children were taked care in an ambulatorial attendance unit, tied with aUniversity, that gives multiprofessional attendance, in a city of average portage in the interior of SãoPaulo. The present study contemplates the stages of the instrument elaboration as well as itsapplications. Its results were described in studies case. The data of the functionality and incapacityevaluation in the related children, beginning from the functions and corporal structures domains, hadshown that the biggest deficiencies were found in the structures related to the movement. These resultsaccording with the findings obtained from the evaluation in the tasks and general demands and mobilitydomains, which had also indicated the difficulties of the participants in the actions that demanded the useof movements of the superior members, except C3, that presented cognitive deficit. Allied to this, thechildren presented more accented difficulties in the actions that demanded the use of global movementsof the inferior members, also in those that demanded balance and sustentation of these members. Inrelation to another component, the environment factors, in the descriptions of the care givers, disclose tohave positive influence in the lives of the children, emphasizing the emotional and material supportoffered by the family and friends. Analyzing the information that had come from the three componentsof the CIF-CJ, it s possible to affirm that, although exists the structure originated from the environmentsfacilitiers, there is also a lack of equipment which the children could be beneficiated to facilitate theaccomplishment of many tasks, in the house as well as in the school. In function of the acquired results,the importance of the evaluation of the functionality and incapacity of the children with physicaldisability is argued, starting from the interaction between the three components: corporal functions andstructures, activity and participation and environment factors, disclosing in the health condition. Thepreschooler in inclusion process health condition detection showed itself as an important tool tostimulate focused care, resulting in better scholar inclusion results. Finally, on the methodological pointof view, the IAFII proved itself adequate for future studies with larger number of participants.
Keywords: Estudantes deficientes físicos; Pré-escolares; Avaliação; Classificação Internacional de Funcionalidade, Incapacidade e Saúde (CIF); Estudantes - atividades; Deficiência física por prematuridade; Inclusão pré-escolar; Desenvolvimento infantil; Atividades; Physical deficiency for prematurity; Preschool inclusion; International Classification of Functionality Disability and Health - Children and Youth (ICF-CY); Children development; Activities; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL